Citizen-centric governance indicators: Measuring and monitoring governance by listening to the people and not the interest groups - Maksym Ivanyna; Anwar Shah (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2009)
Governance indicators are now widely used as tools for conducting development dialogue, allocating external assistance and influencing foreign direct investment. This paper argues that available governance indicators are not suitable for these purposes as they do not conceptualize governance and fail to capture how citizens perceive the governance environment and outcomes in their countries. This paper attempts to fill this void by conceptualizing governance and implementing a uniform and consistent framework for measuring governance quality across countries and over time based upon citizens' evaluations.
Keywords: H10; H11; H83; I31; O10; 330; citizen-centric governance indicators; rule of law; fair governance; service delivery; quality of life; trust in government; government oversight; public opinion